Ex Ante Review in Realizing the Constitutionality of Laws and Regulations in Indonesia - Desy Wulandari (Universitas Negeri Semarang, 2018)
This study aimed to describe the constitutional test models in France and in Indonesia and the prospect of application of the ex ante review in realizing the constitutionality of laws and regulations in Indonesia. The method used by the author is using a normative juridical approach of comparative law. The results showed that the ratio of the most influential position is on the object and the subject of testers. Indonesia's Constitutional Court is subject testers incorporated as a judicial body with the test object in the form of legislation that has been passed and enacted. Whereas in France the Constitutional Council is the subject of testers incorporated as a quasi-judicial body with the test object in the form of draft legislation which has not been enacted. prospects for application of the ex ante review with a name elaborates the basic models of constitutional previews should be considered for implementation in Indonesia, with two alternatives, namely the preview is done by the Constitutional Court or preview conducted by the Legislative Board. This concept is done by a process when a bill has been discussed is obliged to do a preview for the legislation and are non obliged organic law for the non-organic statute law. but the weakness that really stands out is that there is an overlap principle of checks and balances adopted by Indonesia when it is done by the Constitutional Court, and if done by the Legislative Body the authority or the task is still within the scope of the legislature so that they made possible many there is a discrepancy between the bill with Tests of the 1945 Constitution of the draft legislation before it was passed and enacted, consideration of alternative solutions to minimize the unconstitutionality of a law that has been in effect. To accommodate it necessary to do some changes to the 1945 Constitution and the Act governing the MPR, DPR, DPD and DPRD